Amino‐Acid‐Induced Preferential Orientation of Perovskite Crystals for Enhancing Interfacial Charge Transfer and Photovoltaic Performance. Issue 22 (12th April 2017) - Shih, Yen‐Chen; Lan, Yu‐Bing; Li, Chia‐Shuo; Hsieh, Hsiao‐Chi; Wang, Leeyih; Wu, Chih‐I; Lin, King‐Fu
Abstract : Interfacial engineering of perovskite solar cells (PSCs) is attracting intensive attention owing to the charge transfer efficiency at an interface, which greatly influences the photovoltaic performance. This study demonstrates the modification of a TiO2 electron‐transporting layer with various amino acids, which affects charge transfer efficiency at the TiO2 /CH3 NH3 PbI3 interface in PSC, among which thel ‐alanine‐modified cell exhibits the best power conversion efficiency with 30% enhancement. This study also shows that the (110) plane of perovskite crystallites tends to align in the direction perpendicular to the amino‐acid‐modified TiO2 as observed in grazing‐incidence wide‐angle X‐ray scattering of thin CH3 NH3 PbI3 perovskite film. Electrochemical impedance spectroscopy reveals less charge transfer resistance at the TiO2 /CH3 NH3 PbI3 interface after being modified with amino acids, which is also supported by the lower intensity of steady‐state photoluminescence (PL) and the reduced PL lifetime of perovskite. In addition, based on the PL measurement with excitation from different side of the sample, amino‐acid‐modified samples show less surface trapping effect compared to the sample without modification, which may also facilitate charge transfer efficiency at the interface. The results suggest that appropriate orientation of perovskite crystallites at the interface and trap‐passivation are the niche for better photovoltaic performance. Abstract : The (110) plane of CH3 NH3 PbI3 crystallites adjacent to the amino‐acid‐modified TiO2 surface tends to align in the direciton perpendicular to the TiO2 surface. Such crystalline orientation significantly enhances charge transfer efficiency at the TiO2 /CH3 NH3 PbI3 interface and greatly improves the photovotaic performance of perovskite solar cells.